The Effect of Recruitment, Selection and Training Process on Employee Performance - Munaty, Sisna; Dandono, Yustinus Rawi; Setiasih, Setiasih (International Journal of Management and Digital Business, 2022)
This study aims to determine the importance of the recruitment, selection and training of employees in order to increase employee performance at PT. Budiman Sejahtera Development. This research is a quantitative study using SPSS 23 to process data. The sample collection technique used simple random technique. The sample was 44, calculated using the Slovin formula. The results showed that the results of the partial test (t test), there were three variables, namely selection, training of employees which had a positive and significant effect on employee performance, while one variable, namely, recruitment, had a negative and significant value productivity, also found that 98.6% of the influence of the independent variables (recruitment, selection and training of employees) on employee performance and the 11.4% is influenced by other variables not examined.